The Role of Management Information System Implementation on Profitability in SME’s Gendhis Apple Agroindustry, Bumiaji District, Batu City - Maria Natalia Sogara; Gunawan, Cakti Indra; Poppy Indrihastuti (International Journal of Management and Business, 2025)
The implementation of management information systems plays a role in SMEs in the current era of globalization This study aimed to analyze the role of the implementation of the management information system (SIM) on the profitability of Apple Agroindustry SMEs in Batu City. This study used a quantitative descriptive method with primary and secondary data collected through interviews, observations, and documentation. The result showed that the implementation of Management Information System significantly contributes to increasing profitability, which is measured using the Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) ratios. The analysis indicates a Net Profit Margin of 20%, a Return on Assets (ROA) of 42%, and a Return on Equity (ROE) of 67%. These results suggest that the profitability of Gendhis Apple Agroindustry SMEs in Batu City during 2023 was relatively good. A Net Profit Margin of 20% highlights the ability of Gendhis Apple Agroindustry SMEs to achieve significant profits from their revenue. Return On Asset reached 42%, this shows that the Gendhis Apple Agroindustry SMEs are very good in utilizing their assets to generate profits. Return On Equity reached 67%, which shows that the Gendhis Apple Agroindustry SMEs generate high profits from the capital invested by the company owners. The implementation of a Management Information System has positively influenced the profitability of Gendhis Apple Agroindustry SMEs. This would enhance operational efficiency, improve decision-making precision, and strengthen market competitiveness.